2020
DOI: 10.1038/s41598-020-60026-1
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein Reverses Repeated Corticosterone-Induced Depressive-Like Behavior in mice: Evidence of Modulating Effect on Biogenic Amines

Abstract: Depression is still one of challenging, and widely encountered disorders with complex etiology. The role of healthy diet and olive oil in ameliorating depression has been claimed. This study was designed to explore the effects of oleuropein; the main constituent of olive oil; on depression-like behaviors that are induced by repeated administration of corticosterone (40 mg/kg, i.p.), once a day for 21 days, in mice. Oleuropein (8, 16, and 32 mg/kg, i.p.) or fluoxetine (20 mg/kg, positive control, i.p.1) was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 63 publications
(61 reference statements)
2
16
0
Order By: Relevance
“…These disorders are usually characterized by multiple neural disruptions such as neuroanatomical, neurotransmitter, and neuroendocrine alterations (Bandelow et al., 2017; Martin et al., 2009). The neural systems involving regulation of three major monoamine neurotransmitters such as serotonin (5‐HT) (Lawther et al., 2020), DA (Bandelow et al., 2016), and norepinephrine (NE) (Purvis et al., 2018) are the most extensively studied neural systems associated with progression of anxiety. These studies collectively summarizes that hyperactivation of noradrenergic system and under activation of serotonergic system are basically involved in pathology of anxiety (Montoya et al., 2016).…”
Section: Neuroprotective Role Of Oleuropeinmentioning
confidence: 99%
“…These disorders are usually characterized by multiple neural disruptions such as neuroanatomical, neurotransmitter, and neuroendocrine alterations (Bandelow et al., 2017; Martin et al., 2009). The neural systems involving regulation of three major monoamine neurotransmitters such as serotonin (5‐HT) (Lawther et al., 2020), DA (Bandelow et al., 2016), and norepinephrine (NE) (Purvis et al., 2018) are the most extensively studied neural systems associated with progression of anxiety. These studies collectively summarizes that hyperactivation of noradrenergic system and under activation of serotonergic system are basically involved in pathology of anxiety (Montoya et al., 2016).…”
Section: Neuroprotective Role Of Oleuropeinmentioning
confidence: 99%
“…In another study, similar responses were found after treatment with oleuropein at doses of 16 and 32mg/kg, which caused a significant improvement comparable to treatment with fluoxetine (p<0.05). Oleuropein at 16 and 32 mg/kg caused a reduction of approximately 50% in immobility time compared to that of the control group (p <0.001) in FST (Badr, Attia, & Al-Rasheed, 2020).…”
Section: Subtitlementioning
confidence: 83%
“…To assess the depression-like behaviors, we performed the tail suspension test as previously described ( Badr et al, 2020 ). The immobility is a behavioral characteristic associated with depression ( Cryan et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%